2014
DOI: 10.1007/978-3-319-10599-4_31
|View full text |Cite
|
Sign up to set email alerts
|

FPM: Fine Pose Parts-Based Model with 3D CAD Models

Abstract: Abstract. We introduce a novel approach to the problem of localizing objects in an image and estimating their fine-pose. Given exact CAD models, and a few real training images with aligned models, we propose to leverage the geometric information from CAD models and appearance information from real images to learn a model that can accurately estimate fine pose in real images. Specifically, we propose FPM, a fine pose parts-based model, that combines geometric information in the form of shared 3D parts in deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 32 publications
0
59
0
Order By: Relevance
“…A natural approach to estimating the pose of an image I ∈ I is to retrieve the most similar rendered images and use their known camera poses to estimate the pose of I [Aubry et al 2014;Lim et al 2014;Su et al 2014]. We found that the results produced by this approach are noisy, as illustrated in Figure 3.…”
Section: Camera Pose Estimationmentioning
confidence: 99%
“…A natural approach to estimating the pose of an image I ∈ I is to retrieve the most similar rendered images and use their known camera poses to estimate the pose of I [Aubry et al 2014;Lim et al 2014;Su et al 2014]. We found that the results produced by this approach are noisy, as illustrated in Figure 3.…”
Section: Camera Pose Estimationmentioning
confidence: 99%
“…Since our approach is based on object parts, it is also related to works such as [26,27,45,20] that mostly focus on category rather than instance detection. These works were mostly motivated by the success of the Deformable Part Model [7] developed for 2D detection, which was extended successfully to 3D, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Relying on parts for 3D object detection is not new [12,27,33,20,45]. The 1 All the figures of this work are best seen in colors.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations